Nonparametric Statistical Inference with an Emphasis on Information-Theoretic Methods - Mielniczuk, Jan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book addresses contemporary statistical inference issues when no or minimal assumptions on the nature of studied phenomenon are imposed. Information theory methods play an important role in such scenarios. The approaches discussed include various high-dimensional regression problems, time series and dependence analyses.